Potential Overcriminalization in Religious Offenses: A Critical Analysis Of The Formulation Of The New National Criminal Code (Law 1 Number 2023) - Zico Junius Fernando; Sri Wulandari; Panca Sarjana Putra (Jurnal HAM, 2023)
Overcriminalization in the context of criminal law refers to the phenomenon where too many behaviors are defined as criminal offenses, which ultimately results in the expansion of law enforcement powers and an increase in the number of individuals caught up in the criminal justice system. This study examines overcriminalization in the formulation of religious offenses contained in Law Number 1, the Year 2023 on the Criminal Code (KUHP), focusing on Article 302 on incitement of a person to no religion or belief adopted in Indonesia and its impact on atheists or non-religious communities. The analysis highlights several important issues, such as the unclear definition of "inciting" in the article, its impact on freedom of speech, potential discrimination against minorities, and misuse of the law for political purposes. The research was conducted using a qualitative method, combining document studies, literature reviews, and analysis of relevant case law. The results show that Article 302 of the New National Criminal Code may lead to overcriminalization, as it regulates acts that can be considered part of freedom of expression and religion. This article can also be considered as limiting the right of individuals to choose their beliefs or religion, including the right not to have religious beliefs. In addition, this research highlights that this article is vulnerable to abuse by parties who have political interests or want to target specific groups. As a recommendation, this study suggests the need to reform the formulation of Article 302 of the National Criminal Code to reduce the impact of overcriminalization and protect human rights, such as freedom of speech.